1988
DOI: 10.1001/archotol.1988.01860160098030
|View full text |Cite
|
Sign up to set email alerts
|

Skull Metastases From Follicular Thyroid Carcinoma

Abstract: \s=b\Distant metastatic disease from thyroid carcinoma is becoming a rare problem. Physicians and the public are increasingly aware of minimally invasive methods of early diagnosis of thyroid malignancy, such as fine-needle aspiration with cytologic examination. Total thyroidectomy itself has become less associated with morbidity than it once was. We describe three patients with follicular thyroid carcinoma metastatic to the skull who were seen recently. Two of these patients had masses neglected for 20 and 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…24) The metastatic lesion is usually hypervascular and osteolytic on radiological examination. 14) Bleeding is often profuse during surgical resection. 26) The most common symptom of skull base metastasis from FTC is cranial nerve dysfunction, which was observed in 17 of the 19 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24) The metastatic lesion is usually hypervascular and osteolytic on radiological examination. 14) Bleeding is often profuse during surgical resection. 26) The most common symptom of skull base metastasis from FTC is cranial nerve dysfunction, which was observed in 17 of the 19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The lung is the most common metastatic site for thyroid carcinoma followed by the bone, 7,10,26,27) but skull metastasis of thyroid carcinoma is rare, with few reported cases. [1][2][3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]25,26,[28][29][30][31][32][33][34][35][36][37][38]40,41,44,45) The largest series of skull metastasis from thyroid carcinoma reported a frequency of only 2.5% among 473 patients. 26) Moreover, skull base metastasis from differentiated thyroid carcinoma is even rarer, with only 23 reported cases, including 17 cases of skull base metastasis from FTC that involved the clivus, cavernous sinus, sella turcica, petrous apex, and petrous ridge.…”
Section: Introductionmentioning
confidence: 99%
“…15,24,26 Prior studies have assessed the prognostic factors associated with systemic metastasis from thyroid carcinoma; however, none have specifically investigated the factors that affect survival in patients undergoing surgery for spinal metastases. 3,5,13,16,18,21,25,32,36,39,40 Therefore, the objective of this study was to analyze a series of consecutive patients who underwent surgery for spinal metastasis from thyroid cancer in order to identify factors associated with postoperative survival and complications. This prognostic information may aid in clinical decision making, as patients with a more favorable prognosis may warrant more aggressive intervention and patients with poor life expectancy may be spared from aggressive surgery.…”
mentioning
confidence: 99%
“…The metastatic mass may invade the epidural space but the dura forms a barrier to further intracranial spread [9]. Most of these tumours are located in the posterior portion of the cranium and fed primarily from the external carotid artery system [8][9][10][11] [15]. Gates suggested that the apparent predilection for the scalp could be due to the vascularity and relative immobility of the skin at this site [16].…”
Section: Discussionmentioning
confidence: 99%